Knowledge, Attitude, and Practices of Oral and Maxillofacial Surgeons Regarding Behavior Guidance Techniques for Managing Child Patients - Ebru Delikan; Ayşe Özcan Küçük; Aydın Keskinrüzgar (Cumhuriyet University, 2018)
Objectives:The aim of this study was to evaluate the knowledge, attitude, and practices of oral and maxillofacial surgeons regarding behavior guidance techniques that reduced fear and anxiety for children. Materials and Methods:In this cross-sectional study, the participants were oral and maxillofacial surgeons who treat pediatric dental patients in the private and public clinics in Turkey. The questionnaires were applied through an electronic form via a website. The results were evaluated using IBM SPSS Statistics 22 for statistical analysis. A p-value of <0.05 was accepted as statistically significant.Results:60% of the participants were specialist trainees, 9% were doctoral students, 16% were oral and maxillofacial surgeons and 15% were lecturers in the department of oral and maxillofacial surgery of various universities. 45% of the oral and maxillofacial surgeons said they could always take responsibility of working on a pediatric patient, while 33% of them stated that they frequently treated child patients, and 22% of them sometimes took this responsibility. 55% of the participants said they had been trained in behavior guidance techniques for children. The result showed that 93% of the surgeons used tell-show-do, 69% used voice control, 27% used nonverbal communication, 73% used positive reinforcement, 61% utilized distraction techniques, 59% used presence-absence of parents, 15% used hand-over-mouth, 36% used sedation, 36% used restrain/protective stabilization, 46% used general anesthesia, and 2% had used hypnosis method.Conclusions:This study showed that the oral and maxillofacial surgeons working in public and private clinics have a high awareness of behavior guidance techniques while the level of this awareness varies among surgeons according to age, gender, workplace, work experience, and training.